Efficient Cost Allocation - Ray, Korok; Goldmanis, Maris (Management Science, 2012)
Firms routinely allocate the costs of common corporate resources down to divisions. The main insight of this paper is that any efficient allocation rule must reflect the firm's underlying cost structure. We propose a new allocation rule (the polynomial rule), which achieves efficiency and approximate budget balance. Welfare losses due to linear allocation rules increase with firm size, so polynomial allocation rules dominate linear rules for larger firms. This paper was accepted by Mary E. Barth, accounting.